The Struggle for Wealth and Power in the Age of Black Gold - Thalal, Muhammad; Husaini, Husaini; Kurdi, Muliadi; Mursyidin, Mursyidin (SCAD Independent, 2022)
This article discussed the historiography of oil history presented in this review article. This article aimed to demonstrate that oil historians are continually conversing with one another through their publications, even if it is not always visible. This historiographical perspective was supposed to provide a valuable framework for understanding this debate. This article used descriptive analysis in analyzing data to examine major disputes in oil history and how interpretations of those debates have influenced the trajectory of oil history and diplomatic and economic events. The Prize, a famous work by Daniel Yergin, focused on the article's debate. The goal was to examine historical events or topics in oil history from many angles, drawing on several sources that have affected historians' contributions to the field. According to the article, Oil has always been linked to a quest for money and power. The global economy, the result of conflicts, and the political landscape of states were altered by this battle. This study showed that a never-ending attempt to secure Oil, as long as it is vital to human civilization, would eventually lead to wars and conflicts.